Pengaruh Kualitas Pelayanan Dan Sarana Prasarana Terhadap Kepuasan Wisatawan Di Mangrove Watubaing - Mau, Alfonsa Firmina; Rangga , Yoseph Darius Purnama; Lewar , Maria Viviana N. (Jurnal Projemen UNIPA, 2026)
This study aims to determine and analyze the effect of service quality and infrastructure on tourist satisfaction in Mangrove Watubaing.. The background of this study is based on fluctuations in the number of visitors to Mangrove Watubaing tourism and the gap between expectations and reality felt by tourists regarding service quality and tourism facilities. Service quality and infrastructure are important factors in creating comfort and tourist satisfaction during their visit.. This study uses a quantitative approach with causal associative research type. The population in this study were all tourists visiting Mangrove Watubaing. The sampling technique used was accidental sampling with 100 respondents. Data collection techniques were carried out through questionnaires, interviews, and observations . Data analysis techniques used are descriptive statistical analysis, validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, and F-test using SPSS program. The results showed that service quality had a positive and significant effect on tourist satisfaction with a significance value of < 0.05 . Infrastructure also has a positive and significant effect on tourist satisfaction with a significance value of < 0.05. Simultaneously, service quality and infrastructure have a significant effect on tourist satisfaction with an F-count value > F-table and a significance level of < 0.05 [cite: uploaded:SKRIPSI revisi 1.docx]. This shows that the better the quality of service and the more adequate the available infrastructure, the level of tourist satisfaction will increase.